2013
DOI: 10.3945/jn.112.173302
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits IgE-Mediated Basophilic Mast Cell Degranulation and Passive Cutaneous Anaphylaxis in Mice

Abstract: Resveratrol is a phytoalexin abundantly found in red grape skin and is effective in antitumor and antiinflammation associated with immune responses. This study investigated whether resveratrol suppressed immunoglobulin (Ig)E-mediated allergic responses and passive cutaneous anaphylaxis (PCA) in rat RBL-2H3 mast cells and in BALB/c mice. The release of β-hexosaminidase and histamine was enhanced in mast cells sensitized with anti-dinitrophenyl (DNP)-IgE and subsequently stimulated by DNP-human serum albumin (HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 32 publications
4
40
1
Order By: Relevance
“…It was investigated to determine whether imidacloprid treatment could inhibit mast cell degranulation by measuring the release of β-hex and histamine from RBL-2H3 cells [31]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was investigated to determine whether imidacloprid treatment could inhibit mast cell degranulation by measuring the release of β-hex and histamine from RBL-2H3 cells [31]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This method was previously used to document the effect of other inhibitors on MC activation 40 as well as of resveratrol on passive cutaneous anaphylaxis in mice 55 Moreover, the flavonoid concentrations used here in this mouse “model” (100 mg/kg) have already been shown to have a statistically significant benefit at least for lut in children with autism 56 many of whom have been reported to have “allergic-like” symptoms 57 implicating MC activation. 58 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that patients treated with resveratrol had significantly decreased IgE and IL-4 levels in the blood, suggesting that resveratrol inhibited IgE and IL-4 production. Han et al [29] reported that resveratrol inhibits IgE-mediated basophilic mast cell degranulation . This could be another mechanism that contributes to inhibition of AR.…”
Section: Discussionmentioning
confidence: 99%